Pendekatan Integratif Revitalisasi Sanitasi dan Penguatan Manajemen dalam Meningkatkan Mutu Pembelajaran di Pesantren Amrullah Akbar Rajasyah - Amrizal Amrizal; Khairul Rahmi; Zulhendri Zulhendri; Bintarto Purwo Seputro; Elkadi Elkadi (Jurnal Ilmiah Madiya (Masyarakat Mandiri Berkarya), 2026)
Learning environment quality and institutional management effectiveness are essential factors in improving educational quality, particularly in Islamic boarding schools (pesantren). This community service project aimed to examine the effectiveness of an integrative approach through sanitation revitalization and strengthening of pesantren management at Pondok Pesantren Tarbiyah Islamiyah Amrullah Akbar, Medan. The primary issues identified were the imbalance between sanitation facilities and the number of users, where only 5 out of 15 toilet units were functional for 68 students and 18 teachers, as well as limited institutional management capacity. The program employed a participatory, collaborative approach consisting of four stages: needs assessment, planning, implementation, and evaluation. The results demonstrated that the rehabilitation of four sanitation units and ablution facilities significantly improved environmental hygiene and user comfort. Furthermore, management training enhanced the administrators’ capacity in educational governance and institutional planning. The findings indicate that integrating physical and non-physical interventions provides more effective and sustainable outcomes compared to partial approaches. This study contributes an integrative community empowerment model that can be replicated in other community-based educational institutions, particularly Islamic boarding schools in developing areas.